Case Report: Sustained ventricular arrhythmia in a child supported by a Berlin heart EXCOR ventricular assist device - Silva, Diego Lineker Marquetto; Lemouche, Stephanie Ondracek; Takahashi, Tatiane Yukari; Zanon, Isadora de Campos; Siqueira, Adailson; Machado, Desiree; Azeka, Estela; de Melo, Sissy Lara (Frontiers in Transplantation, 2024)
Mechanical circulatory support is an established therapy to support failing hearts as a bridge to transplantation. Although overall tolerated, arrhythmias may occur after ventricular assist device implantation and can complicate patient management. We report an infant with dilated cardiomyopathy who developed ventricular tachycardia followed by recalcitrant ventricular fibrillation, refractory to comprehensive medical therapy post Berlin Heart EXCOR® (BHE) implant.